Encapsulation of nanoparticles into single-crystal ZnO nanorods and microrods - Liu, Jinzhang; Notarianni, Marco; Rintoul, Llew; Motta, Nunzio (Beilstein Journal of Nanotechnology, 2014)
One-dimensional single crystal incorporating functional nanoparticles of other materials could be an interesting platform for various applications. We studied the encapsulation of nanoparticles into single-crystal ZnO nanorods by exploiting the crystal growth of ZnO in aqueous solution. Two types of nanodiamonds with mean diameters of 10 nm and 40 nm, respectively, and polymer nanobeads with size of 200 nm have been used to study the encapsulation process. It was found that by regrowing these ZnO nanorods with nanoparticles attached to their surfaces, a full encapsulation of nanoparticles into nanorods can be achieved. We demonstrate that our low-temperature aqueous solution growth of ZnO nanorods do not affect or cause degradation of the nanoparticles of either inorganic or organic materials. This new growth method opens the way to a plethora of applications combining the properties of single crystal host and encapsulated nanoparticles. We perform micro-photoluminescence measurement on a single ZnO nanorod containing luminescent nanodiamonds and the spectrum has a different shape from that of naked nanodiamonds, revealing the cavity effect of ZnO nanorod.
Keywords: crystal growth; encapsulation; nanoparticles; photoluminescence; ZnO nanorods

(untitled) - Ahn, M.-W.; Park, K.-S.; Heo, J.-H.; Park, J.-G.; Kim, D.-W.; Choi, K. J.; Lee, J.-H.; Hong, S.-H. (Appl. Phys. Lett., 2008)

(untitled) - Goldberger, J.; Sirbuly, D. J.; Law, M.; Yang, P. (J. Phys. Chem. B, 2005)

(untitled) - Lai, E.; Kim, W.; Yang, P. (Nano Res., 2008)

(untitled) - Voss, T.; Svacha, G. T.; Mazur, E. (Nano Lett., 2007)

(untitled) - Huang, M. H.; Mao, S.; Feick, H.; Yan, H.; Wu, Y.; King, H.; Weber, E.; Russo, R.; Yang, P. (Science, 2001)

(untitled) - Wang, Z. L.; Song, J. (Science, 2006)

(untitled) - Pan, Z. W.; Dai, Z. R.; Wang, Z. L. (Science, 2001)

(untitled) - Huang, M. H.; Wu, Y.; Feick, H.; Tran, N.; Weber, E.; Yang, P. (Adv. Mater., 2001)

(untitled) - Huang, C.-H.; Whang, W.-T. (Mater. Chem. Phys., 2003)

(untitled) - Xu, L.; Guo, Y.; Liao, Q.; Zhang, J.; Xu, D. (J. Phys. Chem. B, 2005)

(untitled) - Liu, J.; Lee, S.; Ahn, Y. H.; Park, J.-Y.; Koh, K. H.; Park, K. H. (Appl. Phys. Lett., 2008)

(untitled) - Dai, G.; Zhang, Y.; Liu, R.; Wan, Q.; Zhang, Q.; Pan, A.; Zou, B. (J. Appl. Phys., 2011)

(untitled) - Chu, S.; Wang, G.; Zhou, W.; Lin, Y.; Chernyak, L.; Zhao, J.; Kong, J.; Li, L.; Ren, J.; Liu, J. (Nat. Nanotechnol., 2011)

(untitled) - Taylor, J. M.; Cappellaro, P.; Childress, L.; Jiang, L.; Budker, D.; Hemmer, P. R.; Yacoby, A.; Walsworth, R.; Lukin, M. D. (Nat. Phys., 2008)

(untitled) - Cerdán, L.; Enciso, E.; Martín, V.; Bañuelos, J.; López-Arbeloa, I.; Costela, A.; García-Moreno, I. (Nat. Photonics, 2012)

(untitled) - Brossard, F. S. F.; Xu, X. L.; Williams, D. A.; Hadjipanayi, M.; Hugues, M.; Hopkinson, M.; Wang, X.; Taylor, R. A. (Appl. Phys. Lett., 2010)

(untitled) - Jia, R.; Jiang, D.-S.; Tan, P.-H.; Sun, B.-Q. (Appl. Phys. Lett., 2001)

(untitled) - Henderson, M. R.; Gibson, B. C.; Ebendorff-Heidepriem, H.; Kuan, K.; Afshar, S.; Orwa, J. O.; Aharsonovich, I.; Tomljenovic-Hanic, S.; Greentree, A. D.; Prawer, S.; Monro, T. M. (Adv. Mater., 2011)

(untitled) - Yu, H. C. Y.; Argyros, A.; Barton, G.; van Eijkelenborg, M. A.; Barbe, C.; Finnie, K.; Kong, L.; Ladouceur, F.; McNiven, S. (Opt. Express, 2007)

(untitled) - Li, Q.; Kumar, V.; Li, Y.; Zhang, H.; Marks, T. J.; Chang, R. P. H. (Chem. Mater., 2005)

(untitled) - Lincot, D. (MRS Bull., 2010)

(untitled) - Kozhummal, R.; Yang, Y.; Güder, F.; Hartel, A.; Lu, X.; Küçükbayrak, U. M.; Mateo-Alonso, A.; Elwenspoek, M.; Zacharias, M. (ACS Nano, 2012)

(untitled) - Nobis, T.; Grundmann, M. (Phys. Rev. A, 2005)

(untitled) - Liu, J.; Ngo, Q. M.; Park, K. H.; Kim, S.; Ahn, Y. H.; Park, J.-Y.; Koh, K. H.; Lee, S. (Appl. Phys. Lett., 2009)